Group-based trajectory analysis of acute pain after spine surgery and risk factors for rebound pain - Li, Yi-Shiuan; Chang, Kuang-Yi; Lin, Shih-Pin; Chang, Ming-Chau; Chang, Wen-Kuei (Frontiers in Medicine, 2022)
Background This retrospective study was designed to explore the types of postoperative pain trajectories and their associated factors after spine surgery. Materials and methods This study was conducted in a single medical center, and patients undergoing spine surgery with intravenous patient-controlled analgesia (IVPCA) for postoperative pain control between 2016 and 2018 were included in the analysis. Maximal pain scores were recorded daily in the first postoperative week, and group-based trajectory analysis was used to classify the variations in pain intensity over time and investigate predictors of rebound pain after the end of IVPCA. The relationships between the postoperative pain trajectories and the amount of morphine consumption or length of hospital stay (LOS) after surgery were also evaluated. Results A total of 3761 pain scores among 547 patients were included in the analyses and two major patterns of postoperative pain trajectories were identified: Group 1 with mild pain trajectory (87.39%) and Group 2 with rebound pain trajectory (12.61%). The identified risk factors of the rebound pain trajectory were age less than 65 years (odds ratio [OR]: 1.89; 95% CI: 1.12–3.20), female sex (OR: 2.28; 95% CI: 1.24–4.19), and moderate to severe pain noted immediately after surgery (OR: 3.44; 95% CI: 1.65–7.15). Group 2 also tended to have more morphine consumption (p < 0.001) and a longer length of hospital stay (p < 0.001) than Group 1. Conclusion The group-based trajectory analysis of postoperative pain provides insight into the patterns of pain resolution and helps to identify unusual courses. More aggressive pain management should be considered in patients with a higher risk for rebound pain after the end of IVPCA for spine surgery.